KONGLOMERASI MEDIA DAN POLITIK: ANALISIS KOMODIFIKASI TV SATELIT BERLANGGANAN INDOVISION DALAM PESTA DEMOKRASI - Agusta, Rivga (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Media ownership is closely related to political-economic interests. Whether it involves power over the economic industry that encompasses its fields, as well as power in the political sphere. Ownership of subscription satellite TV also has its own advantages in the sphere of media-political economy. In the momentum of the 2014 legislative and presidential elections, subscription satellite TV Indovision as a subsidiary of broadcast media owned by Harry Tanoesodibjo has its own role. In this article, Indovision's role in the democratic party was analyzed by looking at the theory of commodification of audiences and the commodification of content, both of which are interrelated in perfecting the commodification of political advertising content in Indovision subscription TV. The analysis was carried out using a qualitative descriptive research method with the presentation of several points, including Indovision Domination in the Subscribed Satellite TV Market; Indovision Commodification (covering commodification of audiences and content); and Commodification of Political Advertising Content. Keywords: Political Economy of Media,, TV Cable, Content Commocification, Audiens Commodification.